Investigating Leachate Transport at Landfill Site Using HYDRUS-1D - Anwar, Faisal; Thien, L. (2015)
Landfill leachate is a very common environmental problem that might contaminate underlying soil and groundwater. This paper investigates the potential leachate of heavy metals from the landfill site of Rottnest Island in Western Australia. The heavy metals selected for this study was Copper and Zinc as high concentration of these metals was found in Rottnest groundwater. The migration of heavy metal leachate through the soil profile was modelled using HYDRUS-1D. The model was developed for site specific conditions of Rottnest Island landfill site for the period 1996-2010 for different soil-water-chemical interaction parameters. The results show that the adsorption coefficient kd (cm3/g) is the most significant parameter that dominates the heavy metal migration in soil. The initial concentration also shows significant effect on leachate contamination. The longitudinal dispersion was found with moderate significance in solute transport but diffusion coefficient has no effect on contaminant migration in soil. However, initial soil moisture and saturated hydraulic conductivity showed minimum effect on leachate transport in this landfill site.